Scripting Approaches in Mathematics Education Mathematical Dialogues in Research and Practice (Advances in Mathematics Education,, 2018)
This book shows how the practice of script writing can be used both as a pedagogical approach and as a research tool in mathematics education. It provides an opportunity for script-writers to articulate their mathematical arguments and/or their pedagogical approaches. It further provides researchers with a corpus of narratives that can be analyzed using a variety of theoretical perspectives. Various chapters argue for the use of dialogical method and highlight its benefits and special features. The chapters examine both "low tech" implementations as well as the use of a technological platform, LessonSketch. The chapters present results of and insights from several recent studies, which utilized scripting in mathematics education research and practice.